2019
DOI: 10.1016/j.molp.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Maize Carbohydrate Partitioning Defective33 Encodes an MCTP Protein and Functions in Sucrose Export from Leaves

Abstract: To sustain plant growth, development, and crop yield, sucrose must be transported from leaves to distant parts of the plant, such as seeds and roots. To identify genes that regulate sucrose accumulation and transport in maize (Zea mays), we isolated carbohydrate partitioning defective33 (cpd33), a recessive mutant that accumulated excess starch and soluble sugars in mature leaves. The cpd33 mutants also exhibited chlorosis in the leaf blades, greatly diminished plant growth, and reduced fertility. Cpd33 encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…In maize, ZmCpd33, a homolog of Arabidopsis QKY, promoted symplastic sucrose export from companion cells into sieve elements. The cpd33 mutants exhibited fewer PD at the companion cell-sieve element interface and excessive carbohydrate accumulation in the leaves [32]. These studies suggest that MCTPs are involved in diverse cellular processes mainly through intercellular or intracellular transport of other regulators.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In maize, ZmCpd33, a homolog of Arabidopsis QKY, promoted symplastic sucrose export from companion cells into sieve elements. The cpd33 mutants exhibited fewer PD at the companion cell-sieve element interface and excessive carbohydrate accumulation in the leaves [32]. These studies suggest that MCTPs are involved in diverse cellular processes mainly through intercellular or intracellular transport of other regulators.…”
Section: Introductionmentioning
confidence: 77%
“…Multiple C2 domains and transmembrane region proteins (MCTPs) contain three to four C2 domains in the N terminus and one to four transmembrane regions in the C terminus. MCTPs are evolutionary conserved proteins and have been identified in both animals and plants [7,21,24,25,[27][28][29][30][31][32]38]. Compared with animals and lower plants, higher plants contain significantly increased number of MCTPs, implying more diverse and specific functions of MCTPs in plant growth and development [7].…”
Section: Sequence Characterization Of Ghmctpsmentioning
confidence: 99%
“…Multiple C2 domains and transmembrane region proteins (MCTPs) contain three to four C2 domains in the N terminus and one to four transmembrane regions in the C terminus. MCTPs are evolutionary conserved proteins and have been identi ed in both animals and plants [7,21,24,25,[27][28][29][30][31][32]38]. Compared with animals and lower plants, higher plants contain signi cantly increased number of MCTPs, implying more diverse and speci c functions of MCTPs in plant growth and development [7].…”
Section: Sequence Characterization Of Ghmctpsmentioning
confidence: 99%
“…The signi cantly increased number of MCTPs in higher plants may meet the requirement for more diverse and speci c functions of MCTPs in regulating various cellular processes in plants [7]. Functional analyses of MCTPs in various plant species demonstrated that MCTPs were involved in promoting owering, regulating shoot meristem development, controlling anther dehiscence, regulating cell growth anisotropy and exporting sucrose into sieve elements [7,24,25,[27][28][29][30][31][32]. GUS and GFP reporter assays of 16 AtMCTPs revealed that even MCTPs with close evolutionary relationship might be expressed in different tissues and some MCTPs might perform redundant or additive functions in certain tissues [7].…”
Section: Diverse Expression Patterns Of Ghmctpsmentioning
confidence: 99%
See 1 more Smart Citation